Navigating Political Beliefs at the Grassroots: A Study of Civil Servants' Perceptions on Democracy and Radicalism in Murung Raya - Ul'zikri, Ahmad Robi; Satriawan, Bismar Harris (Journal of Contemporary Local Politics, 2025)
This study investigates the political beliefs of civil servants in Murung Raya Regency, focusing on their perceptions of democracy, presidentialism, and radical ideological discourse. Grounded in Norris and Inglehart’s Cultural Backlash Theory (2019), the research explores how local bureaucrats respond to ideological shifts and sociopolitical tensions in contemporary Indonesia. Employing a quantitative design, the study surveyed 64 government employees through a structured questionnaire administered after a civic education session. The findings indicate that 82.8% of respondents support the presidential system and the separation of powers, while 79.7% agree that Indonesia’s democratic system, despite its flaws, should be preserved. Notably, 96.9% reject radical ideologies such as the caliphate, affirming the resilience of Pancasila as the state ideology. Moreover, 89.1% prefer presidential governance, and 42.2% favor military-background leaders for national leadership, suggesting a cultural orientation toward political stability. These results confirm the relevance of Cultural Backlash Theory in explaining grassroots political attitudes shaped by modernization anxieties and ideological contestation. This study contributes to the discourse on democratic resilience, offering empirical insights into the beliefs of civil servants who act as frontline agents of the state in safeguarding democratic values at the local level.